HUBUNGAN LINGKAR KEPALA BAYI BARU LAHIR DAN KENAIKAN BERAT BADAN IBU SELAMA HAMIL DENGAN KEJADIANRUPTUR PERINEUM DI BPM “Z” BENGKULUTAHUN 2014 - Ratna Dewi (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
The incidence of ruptur in Indonesia which is only about 5% of all deliveries in Indonesia. The most important cause of maternal mortality in Indonesia is 40-60% of bleeding, including bleeding because of the birth canal laceration 4-5%. Objective of this study was to determine the relationship head circumference of newborns and maternal weight gain during pregnancy with rupture of the perineum in BPM Z.type of research is analytic with case control study design. The population in this study all mothers who gave birth in BPM